Prevalence of M. tuberculosis and Associated Risk Factors Among Suspected Patients in Federal Medical Centre Birnin Kudu, Jigawa State. - Obadire Samuel Olalere* , Mitsan Olley , Oke Olakunle Clement ,Ige Ilesanmi Paul (Sokoto Journal of Medical Laboratory Science)
Tuberculosis (TB) stands as a major global health problem, ranking as the second highest cause of death from an infectious disease globally, after the human immunodeficiency virus (HIV). The aim of this study was to identify mycobacteria tuberculosis at the molecular level in symptomatic presumptive TB subjects in Federal Medical Centre, Birnin Kudu Jigawa State, Nigeria. A cross-sectional study was conducted between April to December, 2019 at the Federal Medical Centre Birnin – Kudu (FMC, BKD), Jigawa State. Subjects presenting with any of the following symptoms were recruited: the presence of symptoms suggestive of TB like chronic cough for a period of ≥ 2 weeks, night sweats, fatigue, unexpected loss of weight, and fever. Each eligible subject (272) who signed written consent and provided clinical specimens were recruited into the study. Four milliliters (4ml) of sputum sample were collected. In the case of presumptive extra-pulmonary TB, four milliliters of either pus, CSF samples was collected. Samples were immediately processed for Gene Xpert MTB/RIF assay. Testing for HIV was done according to the current national algorithm recommended by the Federal Ministry of Health of Nigeria. Total number of 52 subjects were M. tuberculosis positive with a total prevalence of 19.1% and total prevalence of 1.1% rifampicin resistance. Most 157 (57.7%) were males. Age groups 20-29, 30-39, and 40-49 have TB positivity rate of 33.5%, 26.5%, and 12.9% respectively. Majority 194 (71.3%) of participants were rural dwellers. Prevalence of HIV was 50 (18.4%) among study participants. The measure of association showed that there was significant association (p<0.05) between TB positivity with type of residence, history of previous TB treatment and reason for diagnosis. Urban residents were 3.23 times likely of being TB positive compared to rural dwellers. The prevalence of Rifampicin-resistant M. tuberculosis is low in pulmonary tuberculosis cases in the study area.